Pharmacokinetics of Dantrolene in the Plasma Exchange Treatment of Malignant Hyperthermia in a 14-Year-Old Chinese Boy: A Case Report and Literature Review - Li, Xiaoxiao; Li, Chao; Zhou, Yang; Li, Zhengqian; Xiong, Xin; Wang, Chuhui; Zhou, Congya; Han, Bin; Yang, Li; Guo, Xiangyang (Frontiers in Medicine, 2022)
Malignant hyperthermia (MH) is a rare life-threatening response that triggered by exposure to specific anesthetics commonly used during surgery interventions. Dantrolene is a well-known drug used as the first-line therapy for MH. A 14-year-old Chinese boy with a mutation in RYR1 whose muscle biopsy diagnosis was central core disease occurred MH after cervical spine surgery, even though he underwent a general anesthesia without volatile anesthetics or succinylcholine. The MH crisis treatment workflow was started and intravenous dantrolene was used soon which combined with sequent continuous veno-venous hemofiltration (CVVH) and plasma exchange (PE) therapy. We explored the pharmacokinetic profile of dantrolene during PE treatment. It showed that a one-compartment model with first-order kinetics was sufficient to characterize dantrolene pharmacokinetics. The renal clearance estimate for dantrolene was 0.33 mL/(min*kg) and volume of distribution was 0.51 L/kg. Though a 4-hour PE elevated about 27% of clearance for dantrolene, it eliminated an extra dantrolene by a mere 4% of area under the curve. We made no recommendation with respect to adjust dantrolene dosing for MH adolescents with a 4-hour PE.